Bioactivity studies and chemical constituents of Murraya paniculata (Linn) Jack - Ng, Mei Kee; Abdulhadi Noaman, Yousr; Cheah, Yoke Kqueen; Yeap, Swee Keong; Mohamed Alitheen, Noorjahan Banu (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Murraya paniculata (Linn) Jack (Orange Jasmine), known as "Kemuning Putih" in Malaysia, has been widely used as food flavor additive in cuisine by local residences. This is due to the strong fragrances of the leaves which make it suitable to be used in Indian and Malay dishes. Besides as a flavoring, leaves, branches, stem barks and roots of the plant are used in folk medicine to treat dysentery and morning sickness. Flowers of the plants are used in cosmetics. Since 1970's, flavonoids and coumarins were isolated from Murraya paniculata, but no further bioactivity has been tested from the isolated compounds. The aim of this paper is to review and update the research related to chemical constituents and bioactivities of Murraya paniculata (L) Jack.